Immune Cell Infiltration as Signatures for the Diagnosis and Prognosis of Malignant Gynecological Tumors - Liu, Qi-Fang; Feng, Zi-Yi; Jiang, Li-Li; Xu, Tong-Tong; Li, Si-Man; Liu, Kui-Ran (Frontiers in Cell and Developmental Biology, 2021)
Background: Malignant gynecological tumors are the main cause of cancer-related deaths in woman worldwide and include uterine carcinosarcomas, endometrial cancer, cervical cancer, ovarian cancer, and breast cancer. This study aims to determine the association between immune cell infiltration and malignant gynecological tumors and construct signatures for diagnosis and prognosis. Methods: We acquired malignant gynecological tumor RNA-seq transcriptome data from the TCGA database. Next, the “CIBERSORT” algorithm calculated the infiltration of 22 immune cells in malignant gynecological tumors. To construct diagnosis and prognosis signatures, step-wise regression and LASSO analyses were applied, and nomogram and immune subtypes were further identified. Results: Notably, Immune cell infiltration plays a significant role in tumorigenesis and development. There are obvious differences in the distribution of immune cells in normal, and tumor tissues. Resting NK cells, M0 Macrophages, and M1 Macrophages participated in the construction of the diagnostic model, with an AUC value of 0.898. LASSO analyses identified a risk signature including T cells CD8, activated NK cells, Monocytes, M2 Macrophages, resting Mast cells, and Neutrophils, proving the prognostic vale for the risk signature. We identified two subtypes according to consensus clustering, where immune subtype 3 presented the highest risk. Conclusions: We identified diagnostic and prognostic signatures based on immune cell infiltration. Thus, this study provided a strong basis for the early diagnosis and effective treatment of malignant gynecological tumors.